THE LACK OF COMPETITION IN THE NON-SCHEDULED PUBLIC TRANSPORT SECTOR IN ITALY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper explores the impact of regulatory constraints on the non-scheduled public transport sector in Italy, focusing on taxi and chauffeur-driven rental services. Despite extensive market liberalization in other industries, this sector remains subject to strict numerical limitations imposed by municipalities under Law No. 21 of 1992. The resulting scarcity of licenses has fostered a secondary market, inflated costs and restricting market access for new entrants. The article examines the economic consequences of this licensing system, highlighting how it distorts competition, raises consumer prices, and reduces service availability, particularly in major urban centres. Attempts at legislative reform have consistently met resistance from industry stakeholders, preventing meaningful liberalization. Moreover, the practice of acquiring licenses in small municipalities, underscores the inefficiencies and complexities within the current regulatory framework. Through an analysis of legal regulation, market data, and policy implications, this paper argues that comprehensive reform is necessary to enhance competition, improve service quality, and ensure fair access to the market. The findings suggest that removing or significantly increasing the cap on taxi and NCC licenses could lead to greater market efficiency, lower consumer costs, and a more dynamic transport sector.